What caused the decrease in RevPAR during the Recession? An ARIMA with intervention analysis of room supply and market demand. Issue 8 (19th August 2014) - Zheng, Tianshu
Abstract : Purpose: This study attempted to examine whether the increase in hotel room capacity in the U.S. had a significant impact on nationwide aggregated weekly Revenue per Available Room (RevPAR) during the recession of 2007-2009 and forecast average RevPAR, Occupancy, and Average Daily Rate (ADR) for 2013 and 2014. Design/methodology/approach: Using Autoregressive Integrated Moving Average with Intervention analysis technique, this study examined the significance of the fluctuations in weekly RevPAR, room capacity, and market demand through the recent recession and forecasted hotel performance for 2013 and 2014. Findings: The results of time series analysis suggest that the fast growth of room capacity during the recession was one of the main causes of the decrease in RevPAR. The 9, 878 more than expected increase in average weekly number of rooms probably caused at least 0.10 more than expected decrease in average weekly RevPAR. The findings of this study also suggest that the U.S. lodging industry has been facing more severe oversupply since the recession and fully rebound of RevPAR cannot be expected in the very near future. Practical implications: The findings of this study will help stakeholders make more informed decisions to cope with possible future economic downturns. By quantifying the capacity increase and forecasting future market demand, this study provides hotel investors with empirical evidence on the overdevelopment and insights into expected overall hotel performance in next two years. This study has also discussed the cyclical patterns of hotel development during the past two recessions. Originality/value: By identifying overdevelopment as one of the main causes of RevPAR decrease during the recession, this study contributes to the literature by adding an alternative explanation of RevPAR fluctuations and deepens the understanding of the adverse effects overdevelopment has on the lodging industry. The findings of this study will help hotel investors develop more informed future expansion plans.